Pengaruh Good Corporate Governance, Ukuran Perusahaan, dan Struktur Modal terhadap Kinerja Perusahaan - Richo Anwar Fahrudin; Subadriyah Subadriyah (Accounting Study Program, Faculty of Economics and Business, 2020)
This research aims to obtain evidence regarding good Corporate Governance, company size, and capital structure to the performance of manufacturing companies. This analysis uses Independent variables, namely good Corporate Governance, company size, capital structure. The dependent variable is the performance of the company. Determination of samples using purposive sampling methods that aim to make the sample obtained is a representation of the existing population and in accordance with the purpose of the study. The sample selection process is based on criteria. beverage food companies registered with IDX from 2016 - 2018 as many as 64 companies. Based on this calculation there are 50 company data that meet the criteria. Analytical methods are used descriptive statistical tests, classical assumption tests, regression analysis. The results of this study showed that the board of commissioners variables had a positive effect on the company's performance, the board of directors variables negatively affected the company's performance, the company's size variables had no effect on the company's performance.